Adaptation of the Academic Disciplines “General Psychology” and “Psychology Workshop” for Students with Disabilities: A Case Study of the “Ukraine” University - Kushchenko, I. V.; Matsiuk, O. L. (Вісник Харківського національного університету внутрішніх справ, 2025)
This article is dedicated to the study of the problems and strategies for adapting the academic disciplines “General Psychology” and “Psychology Workshop” for students with disabilities, using the example of “Ukraine” University, a leading institution in the field of inclusive education. The paper identifies existing barriers faced by these students, including limited accessibility of learning materials, difficulties in understanding theoretical concepts, and the inadequacy of adapted practical tasks and assessment methods. Based on a survey of 30 first-year psychology students with disabilities and a poll of 10 instructors of the relevant disciplines, the effectiveness of current adaptation measures is analyzed, and areas requiring improvement are identified. Students expressed a need for more diverse learning materials (audio, video), an increased number of consultations, and tutoring support. Instructors, while using various adapted teaching methods, emphasized the lack of specialized resources and insufficient time for individual student support. Based on the data obtained, the article proposes practical recommendations for improving the educational process, including expanding access to materials in various formats, enhancing instructor support, optimizing the assessment system, and strengthening technical provision. Specific adaptations for teaching psychological disciplines are suggested, such as the logical structuring of content, the use of multimedia, the application of specialized software, the individualization of learning, and flexible deadlines for tasks. The study confirms the progress of “Ukraine” University in inclusive education but underscores the importance of further development and the implementation of individual adaptation strategies to ensure equal access and a comfortable learning environment for all students, which will ultimately increase the effectiveness of higher education for persons with disabilities. Prospects for further research include expanding opportunities for distance learning, developing specialized educational materials, integrating digital technologies, and strengthening psychological support for students.